Dynamics of Management of Muhammadiyah Islamic Education Institute - Siddik, Zulkarnaen Ali; Ansori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to explain the dynamics of the management of Muhammadiyah Education Institutions. This research type is qualitative with a library research approach. The research data is in data form on the Dynamics of Muhammadiyah Education Institutions in management aspects from primary sources in the form of relevant books and journals. Data collection techniques are carried out with documentation. Sources of research data were obtained from books and journals on the Dynamics of Muhammadiyah Educational Institutions in management aspect. Data analysis using Content Analysis. Based on the descriptions made, it is concluded that since its establishment, Muhammadiyah educational institutions have continued to develop and increase both in quantity and quality, but there are also institutions that have experienced setbacks and even closed. This is the dynamics of educational institutions that must be accepted. So far, the management used by Muhammadiyah has made the founders of Muhammadiyah schools eager to compete. However, according to the author, the current management needs to be thoroughly evaluated to improve the quality of Muhammadiyah education as a whole.